Social ethics : morality and social policy - Mappes, Thomas A.; DeGrazia, David; Zembaty, Jane S. (McGraw-Hill, 2012)
With an assortment of readings and perspectives from some of the respected thinkers of our time, this title provides a balanced introduction to the pressing social and moral problems. It illuminates the issues at the heart of each problem and encourages critical, fair-minded examination of varying viewpoints